Coordinated down-regulation of the antigen processing machinery in the gills of amoebic gill disease-affected Atlantic salmon (Salmo salar L.) - Young, ND; Cooper, GA; Barbara Nowak; Koop, BF; Morrison, RN (2008)
Several important cultured marine fish are highly susceptible to an ectoparasitic condition known as amoebic gill disease (AGD). In AGD-affected fish, modulation of IL-1Î², p53 and p53-regulated transcripts is restricted to the (multi)focal AGD-associated gill lesions. To determine whether this lesion-restricted modulation of transcripts occurs on a transcriptome-wide scale and to identify mechanisms that underpin the susceptibility of fish to AGD, we compared the transcriptome of AGD lesions with "normal" tissue from AGD-affected and healthy individuals. Global gene expression profiling using a 16 K salmonid microarray, revealed a total of 176 significantly regulated annotated features and of those, the modulation of 99 (56%) was lesion-restricted. Annotated transcripts were classified according to functional gene ontology. Within the immune response category, transcripts were almost universally down-regulated. In AGD-affected tissue, significant, coordinated down-regulation of the major histocompatibility complex class I (MHC I) pathway-related genes occurred during the later stages of infection and appeared to be mediated by down-regulation of interferon-regulatory factor (IRF)-1, independent of interferon-Î±, interferon-Î³ and IRF-2 expression. Within this micro-environment, suppression of the MHC I and possibly the MHC II pathways may inhibit the development of acquired immunity and could explain the unusually high susceptibility of Atlantic salmon to AGD. Â© 2008 Elsevier Ltd. All rights reserved.